Corporate boards in law and practice : a comparative analysis in Europe - Davies, P. L. (Paul Lyndon); Hopt, Klaus J., 1940-; Nowak, Richard; Solinge, Gerard van, 1962- (Oxford : Oxford University Press, 2014)
Corporate boards play a central role in corporate governance and are thus regulated in the corporate law and corporate governance codes of all industrialised countries. This book analyses the corporate boards, their regulation in law and codes and their actual functioning in ten European countries (Belgium, France, Germany, Italy, the Netherlands, Poland, Spain, Sweden, Switzerland, and the United Kingdom). It offers the most up-to-date practical and analytical information on boards in Europe by leading company law experts.
Specialized.
Description based on online resource; title from home page (viewed on January 6, 2014).
Keywords: Corporate governance -- Law and legislation; Boards of directors; Conflict of laws -- Corporations -- Europe; Law; Laws of specific jurisdictions & specific areas of law